Avicenna’s Concepts on Cancer Metastasis from the 11th Century: - Kardeh, Bahareh; Kardeh, Sina (Galen Medical Journal, 2019)
From ancient times to the era of industrialization, medical and philosophical scholars have long been wondering about the nature and the underlying mystery of cancer. Despite the extensive efforts in recent decades trying to shed light on the true histopathologic basis of malignancies, many questions remain to be elucidated. Thus, itâ€™s not surprising that even the most notable predecessor physicians knew only very little about cancer and metastasis. In this paper, we present a brief review of the historical assumptions about the origin and spread of tumoral growths. Subsequently, we will look at an impressing notion by Avicenna about the possibility of local metastasis, which had remained unacknowledged so far and highlights the intellect of this great Persian physician even further. [GMJ.2019;8:e1292]Â 